Cracking in dissimilar laser welding of tantalum to molybdenum. (June 2018) - Zhou, Xingwen; Huang, Yongde; Hao, Kun; Chen, Yuhua
Highlights: Transgranular and intergranular cracks were found in the fusion zone of dissimilar laser welded joint of Ta to Mo. Solidification cracking tendency of Mo is a main reason for crack initiation in the Ta/Mo joint. Low ductility feature of the fusion zone promoted the transgranular propagation of cracking. Abstract: Dissimilar joining of tantalum (Ta) to molybdenum (Mo) is of great interest in high temperature structural component applications. However, few reports were found about joining of these two hard-to-weld metals. The objective of this experimental study was to assess the weldability of laser butt joining of 0.2 mm-thick Ta and Mo. In order to study cracking mechanism in Ta/Mo joint, similar Ta/Ta and Mo/Mo joints were compared under the same welding conditions. An optical microscope observation revealed presence of intergranular cracks in the Mo/Mo joint, while both transgranular and intergranular cracks were observed in Ta/Mo joint. The cracking mechanism of the Ta/Mo joint was investigated further by micro-hardness testing, micro X-ray diffraction and scanning electron microscopy. The results showed that solidification cracking tendency of Mo is a main reason for crack initiation in the Ta/Mo joint. Low ductility feature in fusion zone most certainly played a role in the transgranular propagation of cracking.